Peningkatan Kompetensi Pembelajaran Mata Pelajaran Biologi Tahun Pelajaran 2021 / 2022 - Hananingsih, Titi (LaKaspia, 2023)
This study aims to identify factors influencing Biology learning competencies for the academic year 2021/2022, analyze the effectiveness of teaching methods applied, and evaluate the impact of learning strategies, including the use of technology and pedagogical innovations. Employing a mixed-methods approach, the research involves quantitative methods through surveys and questionnaires, as well as qualitative methods through in-depth interviews and direct observations. The sample consists of Biology students and teachers from several high schools (SMA), selected via purposive sampling. Data is analyzed using descriptive and inferential statistics for quantitative data, and thematic analysis for qualitative data. The results show that teaching quality, student engagement, and the use of technology are key elements in enhancing Biology learning competencies. Teaching methods that involve active learning and multimedia are found to be more effective than traditional methods, with technology such as interactive software contributing to student competency achievement. In conclusion, innovative teaching methods and technology have a significant positive impact. To maximize outcomes, training and support for teachers, along with ongoing evaluation of learning strategies, are necessary. Schools should adopt technology-based methods and support active learning to improve students' competencies in Biology Abstrak Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kompetensi pembelajaran Biologi pada tahun pelajaran 2021/2022, menganalisis efektivitas metode pengajaran yang diterapkan, dan mengevaluasi dampak strategi pembelajaran, termasuk penggunaan teknologi dan inovasi pedagogi. Menggunakan pendekatan campuran, penelitian ini melibatkan metode kuantitatif melalui survei dan kuesioner, serta metode kualitatif melalui wawancara mendalam dan observasi langsung. Sampel penelitian terdiri dari siswa dan guru Biologi di beberapa sekolah menengah atas (SMA) yang dipilih secara purposive sampling. Data dianalisis dengan menggunakan statistik deskriptif dan inferensial untuk data kuantitatif, serta analisis tematik untuk data kualitatif. Hasil penelitian menunjukkan bahwa kualitas pengajaran, keterlibatan siswa, dan penggunaan teknologi merupakan elemen kunci dalam meningkatkan kompetensi pembelajaran Biologi. Metode pengajaran yang melibatkan pembelajaran aktif dan multimedia terbukti lebih efektif dibandingkan metode tradisional, dan penggunaan teknologi seperti perangkat lunak interaktif berkontribusi pada pencapaian kompetensi siswa. Kesimpulannya, metode pengajaran inovatif dan teknologi memiliki dampak positif yang signifikan. Untuk memaksimalkan hasil, diperlukan pelatihan dan dukungan untuk guru serta evaluasi berkelanjutan terhadap strategi pembelajaran. Sekolah sebaiknya mengadopsi metode berbasis teknologi dan mendukung pembelajaran aktif untuk meningkatkan kompetensi siswa dalam mata pelajaran Biologi